Sizing Optimization of Large-Scale Grid-Connected Photovoltaic System Using Cuckoo Search - Muhammad Zakyizzuddin Bin Rosselan; Shahril Irwan Sulaiman; Ismail Musirin (Institute of Advanced Engineering and Science, 2017)
This study presents the development of Cuckoo Search (CS)-based sizing algorithm for sizing optimization of 5MW large-scale Grid-Connected Photovoltaic (GCPV) systems. CS was used to select the optimal combination of the system components which are PV module and inverter such that the Performance Ratio (PR) is correspondingly optimized. The oversized and undersized of this large-scale GCPV system can give huge impact towards the performanceof this system. Before incorporating the optimization methods, a sizing algorithm for large-scale GCPV systems was developed. Later, an Iterative-based Sizing Algorithm (ISA) was developed to determine the optimal sizing solution which was later used as benchmark for sizing algorithms using optimization methods.The results showed that the CS-based sizing algorithm was unable to found the optimal PR for the system if compared with ISA. However, CS was outperformed ISA in producing the lowest computation time in finding the optimal sizing solution.